Gender injustice in Niqula Haddad’s Ḥawwāʾ al-Jadīdah : A radical feminist analysis - Azzahro, Rizqy Aulia; Rohman, Mohamad; Ismatullah, Dadang (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study examines representations of gender injustice in Niqula Haddad’s novel Ḥawwāʾ al-Jadīdah. The purpose of this research is to identify the patterns of oppression depicted in the narrative and analyze how these forms of injustice reflect broader social norms within Arab society. The study employs a descriptive qualitative method and uses Kate Millett’s radical feminist theory as a theoretical framework, which views patriarchy as the fundamental source of women’s subjugation. Data were obtained through library research, involving close reading, annotation, and classification of textual evidence related to gender injustice, followed by analysis of the narrative elements. The findings, analyzed through Kate Millett’s radical feminist framework, reveal five prominent forms of gender injustice experienced by the female characters: marginalization, subordination, negative stereotyping, physical and non-physical violence, and the burden of double work. Marginalization is reflected in the restriction of female characters’ access to rights, mobility, and opportunities. Subordination appears through the positioning of female characters as inferior and powerless within both family structures and broader social systems. Negative stereotyping is manifested in the labeling of women as morally weak, emotionally unstable, or inadequate, which reinforces discriminatory attitudes. Violence is expressed through coercion, harassment, and objectification, indicating how women’s bodies and agency are controlled by male authority. The double burden emerges when female characters are expected to fulfill domestic responsibilities while simultaneously contributing to economic needs without equitable support from men. The study concludes that gender injustice in the novel is not merely an individual experience but a structural manifestation of entrenched patriarchal values embedded in social, cultural, and familial institutions. The study contributes to Arabic literary criticism and feminist discourse by demonstrating how literature reflects and critiques structural gender inequalities in Arab society. This research contributes to feminist literary studies by highlighting the role of Arabic prose in documenting and challenging gender-based injustice, while also encouraging readers to develop greater awareness of the need for social justice.